BRAQUIOPODOS ORDOVICICOS DE LA SIERRA DEL FAMATINA (FORMACION MOLLES), PROV. DE LA RIOJA (Ameghiniana, 2013)
In this article, it is considered a Brachiopods Fauna from Formación Molles, Sistema del Famatina, La Rioja Province. A new genus, Famatinorthis, with a new species F. turneri, two new species of Ortambonitbes, O. mollesensis and O. riojanus and a new species of Mimella, M. nova, are described. This assemblage belongs to Middle Ordovician age (Llanvirnian-Llandeillan). The presence of Ortambonithes and Mimella are mencioned by the first time in Argentine.